Characterization and Optimization of Fe2O3 Extraction From Red Mud Using APDC ligan - prastyo, elli; Yully Mulyani (Prodi Kimia, 2024)
The main component contained in the red mud is Fe2O3 which has the potential to be used as a catalyst in chemical reactions and can be used as a Fe3O4 catalyst manufacture. One method that can separate ferrous metal (Fe) from Red Mud is the extraction method using a chelating agent. This study studied the extraction of Fe2O3 from red mud by solvent extraction method using APDC ligands under various concentration. The variables studied are pH optimization, ligand concentration and extraction time. Analysis of red mud extraction results using FTIR, XRF, and XRD on various variables. Determination of the maximum wavelength of complex compounds formed between Fe(III) ions and ammonium pyrrolydine dithiocarbamate (APDC) ligands with pH variations of 1, 2, 3, 4, 5, and 6 in the wavelength range of 200 – 450 nm. The resulting complex compound is yellow and obtained a maximum wavelength of 347 nm. The greatest value of Fe2O3 absorbance is obtained at pH 1. The concentration of APDC ligands on the extraction of Fe-APDC complex compounds reached optimum conditions at a concentration of 0.5 mM with an optimum extraction time of 5 min. The FTIR spectrum formed in the Fe2O3 compound from the extraction is shown by the presence of vibration peaks in the regions of 447 cm-1 and 524 cm-1. Analysis of XRD Fe2O3 extraction results from red mud showed that the dominant phase was hematite (Fe2O3) followed by the minor phase of SiO2.